(untitled) (Experimental biology, 2024)
The Republic of Kazakhstan has adopted and put into effect the Law of the RK No. 122-VII dated May 21, 2022 “On Biological Safety of the Republic of Kazakhstan”, regulating and defining at the state level the basic principles and preventive measures to protect the population from possible biological threats, assessment and prediction of biological risks in the country. In modern conditions of global real epidemic (COVID-19) biological threats, as never before, there is an urgent need to develop standard methods for assessing, modeling and forecasting biological risks necessary for the organization and implementation of preventive measures for the biological protection of people living in areas unfavorable for natural focal infections. This publication announced the results of research work on the development of a concept (working hypothesis) of a mathematical model for assessing biological risks and predicting the activity of endemic natural foci of the CCHF in certain administrative regions of the Turkestan region. It is assumed that the developed model of mathematical modeling will undergo statistical validation and adjustment based on the incidence rates of the population and the infection of ticks with the CCHF virus, obtained following the results of the epidemic season in August-September 2023 in the endemic territories of Zhambyl, Kyzylorda and Turkestan regions.